2005
DOI: 10.1111/j.1365-2389.2005.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Ag, In, Sn, Sb and Bi, and their chemical fractionation in typical soils in Japan

Abstract: We determined concentrations of Ag, In, Sn, Sb and Bi, and fractionated them by sequential extraction procedures, in five Japanese soils: Andosol-1 (grassland), Andosol-2 (forest), Cambisol (forest), Fluvisol (vegetable garden) and Regosol (forest). Average concentrations of Ag, In, Sn, Sb and Bi were 0.17 AE 0.08, 0.081 AE 0.019, 2.2 AE 0.5, 0.83 AE 0.32 and 0.32 AE 0.12 mg kg À1 , respectively. Average distributions of the chemical fractions (omitting those with an abundance < 5%) were: Ag, residualProportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 40 publications
4
19
0
Order By: Relevance
“…In contrast, the results of this study showed that the fraction of Bi bioaccessible in soil, and consequently the fraction of Bi bioavailable to uptake by soils organisms increased despite the pH rise induced by earthworm activity. The rise in soil pH might increase the mobility of metals including Bi, due to an increase in the number of pH-dependent cation-exchange sites on the soil surface as suggested by Hou, et al [11]. Indeed, the present Bi study showed an increase in earthworm lethality with the increase of soil pH ( Fig.…”
Section: Total and Bioaccessible Bi In Soilsupporting
confidence: 59%
See 2 more Smart Citations
“…In contrast, the results of this study showed that the fraction of Bi bioaccessible in soil, and consequently the fraction of Bi bioavailable to uptake by soils organisms increased despite the pH rise induced by earthworm activity. The rise in soil pH might increase the mobility of metals including Bi, due to an increase in the number of pH-dependent cation-exchange sites on the soil surface as suggested by Hou, et al [11]. Indeed, the present Bi study showed an increase in earthworm lethality with the increase of soil pH ( Fig.…”
Section: Total and Bioaccessible Bi In Soilsupporting
confidence: 59%
“…This was not observed using the sandy soil, where nitric acid failed to dissolve the sand particles. The link between extractability of heavy metals from soil and the size of soil particles was reported earlier [11,41,42]. However, it is widely acknowledged that the total content of metals in soil is not a relevant parameter to determine potential risks from soil contamination.…”
Section: Total and Bioaccessible Bi In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…A sequential extraction scheme was used to investigate the Ag fractionation of five Japanese soils [68]. Mean concentrations of Ag in the chemical fractions were; 0.8 % exchangeable, 0.5 % carbonate bound, 20.9 % organically bound, 8.8 % oxide-bound, and 60.3 % residual.…”
Section: Sorption-desorption Reactionsmentioning
confidence: 99%
“…Moreover, they found that the major fraction of soil-sorbed Sn was associated with OM or Al/Fe-(hydro) oxide fractions. Hou et al (2006) showed that Sn occurred in relatively diverse fractions, and the concentrations of Sn in the residues were large in clay-rich soils. They found that the average proportions of the mobilizable (exchangeable, carbonate-bound, metal-organic complex, easily reducible metal oxide-bound) fractions of Sn was 36 ± 16%, whereas 40 ± 13% associated with the residues.…”
mentioning
confidence: 98%